1994
DOI: 10.1115/1.2910855
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of a Micro Heat Pipe

Abstract: A detailed mathematical model is developed in which the heat and mass transfer processes in a micro heat pipe (MHP) are examined. The model describes the distribution of the liquid in a MHP and its thermal characteristics depending upon the liquid charge and the applied heat load. The liquid flow in the triangular-shaped corners of a MHP with polygonal cross section is considered by accounting for the variation of the curvature of the free liquid surface and the interfacial shear stresses due to a liquid-vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(67 citation statements)
references
References 0 publications
4
63
0
Order By: Relevance
“…For predicting thermal characteristics of heat pipes with various cross-sectional and groove shapes, many researchers have suggested simplified one-dimensional theoretical models based on the differential form of the Laplace-Young equation [3][4][5][6][7][8]. In order to facilitate the analysis, these models employ many simplifying assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…For predicting thermal characteristics of heat pipes with various cross-sectional and groove shapes, many researchers have suggested simplified one-dimensional theoretical models based on the differential form of the Laplace-Young equation [3][4][5][6][7][8]. In order to facilitate the analysis, these models employ many simplifying assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Peterson [31] experimentally validated the model proposed by Khrustalev and Faghri [29]. They demonstrated that for nearly maximum thermal loads, a very high fraction of the liquid pressure drop occurred in the evaporator and the beginning of the adiabatic section.…”
Section: Thermal Capacitymentioning
confidence: 96%
“…A detailed mathematical model for the analysis of a micro heat pipe, which described the liquid distribution and thermal characteristics in relation to the liquid charge and heat load, was developed by Khrustalev and Faghri [101]. The variation in curvature of the free liquid surface as well as the interfacial shear stress due to liquid-vapor frictional interaction were represented in the model.…”
Section: Micro Heat Pipesmentioning
confidence: 99%